Factors of Self-Confidence and Aggressive Traits - Vukičević, Leposava; Mihajlović, Dragica (Zbornik Instituta za kriminološka i sociološka istraživanja, 2012)
It is hard not to notice that the signs of violence at schools, in our environment, from year to year are becoming more and more brutal. Trying to fully examine the psychological basis of the manifestation of traits of aggression, in this study, we investigated the association of different aspects of self–expression, self–confidence, and traits of aggression in high school adolescents. Research has been done at the sample which included 175 students of selected high schools in Belgrade, aged between 15 and 19 years. The level of self-esteem was measured using six different scales, which cover different aspects of self-confidence. These are: Scale of the need to belong, Scale of anxiety in the interaction, Scale of anxiety about physical appearance, Scale of emotional vulnerabilities, Scale of false representation and Scale of tendency to blush. Measuring instruments used in this study showed high reliability which is from α=0.869 for Scale of aggression BAPG (Buss i Perry, 1992) to the α=0.878 for set of scales that we used to investigate the self-confidence. The results showed a significant positive correlation between "False representation" as a manifestation of lack of confidence and the following factors, measured on a scale of aggressiveness: "Hostility", "Anger", and "Physical aggression". It was noticed that the "Social anxiety in interacting with others" also has a positive correlation with factors of aggression: "Hostility" and "Anger". "Social anxiety caused by physical appearance" is also positively correlated with these two factors: "Hostility" and "Anger". Confidence builds and manifests itself in relation to others. The results showed that the lack of confidence is really linked to some forms of expression of traits of aggression. This correlation suggests the possibility that such behaviour has a compensatory role for the person who manifests it. Students who have a lack of confidence expressed through false representation, social anxiety caused by interacting with others and physical appearance, also have a bigger tendency to express their traits of aggression.